A non–destructive compositional analysis of thin surface films formed on W–xTa alloys by angle resolved X–ray photoelectron spectroscopy - Bhattarai, Jagadeesh (BIBECHANA, 2012)
Synergistic effect of the simultaneous additions of tungsten and tantalum in the extremely high corrosion resistance properties of the spontaneously passivated sputter–deposited W–xTa alloys was investigated using a non-destructive angle resolved X-ray photoelectron spectroscopy (angle resolved XPS) techniques in this study. In-depth surface analyses of the thin passive films formed on the spontaneously passivated amorphous/nanocrystalline W–xTA alloys using angle resolved XPS analyses revealed that the high corrosion resistance of the alloys is mostly due to the formation of homogeneous passive double oxyhydroxide films consisting of Wox and Ta4+ cations with a small concentration gradients in–depth particularly after immersion between 20–168 h in 12 M HCl solution open to air at 30°C. Consequently, tantalum metal acts synergistically with tungsten in enhancing the spontaneous passivity as well as the high corrosion resistance of the sputter–deposited binary W–xTa alloys in 12 M HCl solution. Keywords: Sputter deposition; W–xTa alloys; 12 M HCl; Take-off angle DOI: http://dx.doi.org/10.3126/bibechana.v8i0.4784 BIBECHANA 8 (2012) 8-16